«Green roofs» - historical experience and modern requirements - Filonenko, Olena; Avramenko, Yurii; Kidenko, Vitalii (Academic journal Industrial Machine Building Civil Engineering, 2020)
The article considers the historical experience of creating "green roofs", as well as the requirements and conditions under which such roofs are currently designed. Historical examples and existing modern world objects show the expediency of creating and using green roofs of houses in Ukraine, which will significantly enrich the "fifth facade" of buildings and improve the overall appearance of cities. The lack of regulatory framework for the design of "green roofs", as well as some types of roofing technology problems that may arise during the operation of such roofs and the consequences that they have - environmental, economic, social, and technical. Determining the design conditions and the feasibility of using "green roofs" was chosen a structural scheme of combined coverage, which has all the necessary structural elements. It has been shown that the energy efficiency of this type of coating is provided. Determination of heat transfer resistance was carried out according to all regulatory requirements of SBC B.2.6 - 31: 2006. Constructions of houses and buildings, thermal insulation of buildings. The structural component of the designed "green roof" and the sequence of arrangement of some structural layers of this type of coating are considered. The efficiency and expediency of installation of "green" coatings on residential buildings, as well as the standard service life and warranty period of maintenance-free service of this coating, subject to regulatory requirements and operating conditions.
Keywords: energy efficiency; green roofs; green structures; landscaping; environmental improvement